Serum Atypical Pseudocholinesterase and Genetic Factors in Leprosy. Issue 5823 (12th August 1972) - Thomas, Molly; Job, C. K.
Abstract : The levels of pseudocholinesterase and its nature were studied in 390 leprosy patients and 343 control subjects. The levels of the enzyme in both leprosy patients and normal controls were comparable. The study of the nature of the enzyme by determining its dibucaine number showed that a statistically significant number of lepromatous patients had the atypical variety of the enzyme compared with normal controls or tuberculoid patients. Since the presence of the atypical variety of the enzyme is genetically determined it is suggested that genetic factors play an important part in deciding susceptibility to lepromatous leprosy.